2018
DOI: 10.1002/jcp.27408
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease after 5/6 nephrectomy disturbs the intestinal microbiota and alters intestinal motility

Abstract: Organ-organ crosstalk is involved in homeostasis. Gastrointestinal symptoms are common in patients with renal failure. The aim of this study was to elucidate the relationship between gastrointestinal motility and gastrointestinal symptoms in chronic kidney disease. We performed studies in C57BL/6 mice with chronic kidney disease after 5/6 nephrectomy. Gastrointestinal motility was evaluated by assessing the ex vivo responses of ileum and distal colon strips to electrical field stimulation.Feces were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 53 publications
(73 reference statements)
1
23
0
Order By: Relevance
“…Of note, antibiotic therapy improved intestinal dysmotility, fecal amounts, and the expression of cytokines. In addition, they reported that in an ex vivo procedure similar to Hoibian's study, an incubation with spermine had a negative impact on intestinal motility, whereas that with IS did not [18]. This discordance may be attributable to the difference in IS concentration and in the incubation time.…”
Section: Gut Dysbiosismentioning
confidence: 87%
See 2 more Smart Citations
“…Of note, antibiotic therapy improved intestinal dysmotility, fecal amounts, and the expression of cytokines. In addition, they reported that in an ex vivo procedure similar to Hoibian's study, an incubation with spermine had a negative impact on intestinal motility, whereas that with IS did not [18]. This discordance may be attributable to the difference in IS concentration and in the incubation time.…”
Section: Gut Dysbiosismentioning
confidence: 87%
“…The expression levels of interleukin-6, tumor necrosis factor-α, and inducible nitric oxide synthesis were increased in the gut of uremic rats. Using the same animal models, Nishiyama et al showed that uremia induced gut dysbiosis, intestinal dysmotility, a decreased amount of feces, as well as intestinal inflammation [18]. Of note, antibiotic therapy improved intestinal dysmotility, fecal amounts, and the expression of cytokines.…”
Section: Gut Dysbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…The negative correlation between IL-6 level and muscle contractility was also verified in an experiment using repeated LPS injection to induce muscularis cross-tolerance to POI. And this relation, mainly via the NF-kB, was not shown in mucosa, indicating the exclusive effects IL-6 exert on the muscularis [77], this phenomenonis also elucidated in UC [78] as well as diseases in other organs [79] and various kinds of colonic damages [80,81].…”
Section: Box 2: Il-6 and Gastrointestinal Motilitymentioning
confidence: 97%
“…For example, isovaleric acid has been shown to cause colonic smooth muscle relaxation in an ex vivo rodent model . In addition, decreased gastrointestinal motility has been linked directly to uremia by causing dysbiosis and colonic inflammation secondary to increased uremic toxin exposure in rodent models . In an ex vivo rodent model, incubation of colons with the gut‐derived uremic toxins IS and pCS, but not urea, was shown to decrease force of contraction by 66% and 55%, respectively .…”
Section: Discussionmentioning
confidence: 99%